Continuance Intention in Mobile Payment Services: A Comprehensive Systematic Literature Review - Dastyn Susanto; Lisana Lisana (Eduvest - Journal of Universal Studies, 2026)
The development of mobile payments has accelerated significantly since the COVID-19 outbreak. Many people have shifted from traditional payment methods such as cash to cashless payments. This study focused on a systematic literature review of existing articles on continuance intention in mobile payments. The review adheres to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines to ensure transparency and reproducibility. Employing a comprehensive search strategy with predefined keywords, a preliminary search yielded 993 papers from Google Scholar. After applying the inclusion criteria, 30 papers published between 2021 and 2025 were selected for final analysis. The findings explain that factors such as perceived usefulness, ease of use, satisfaction, hedonic motivation, trust, and perceived security are the most frequently used and have a significant influence on continuance intention using mobile payments. This review contributes to a deeper understanding of the theoretical and empirical dimensions of user continuance intention in mobile payments. It provides directions for future research and practical implications for service providers.